Temporal processing and context dependency of phoneme discrimination in patients with aphasia - Fink, Martina; Churan, Jan; Wittmann, Marc (Brain and language, 2006)
Standard diagnostic procedures for assessing temporal-processing abilities of adult patients with aphasia have so far not been developed. In our study, temporal-order measurements were conducted using two different experimental procedures to identify a suitable measure for clinical studies. Additionally, phoneme-discrimination abilities were tested on the word, as well as on the sentence level, as a relationship between temporal processing and phoneme-discrimination abilities is assumed. Patients with aphasia displayed significantly higher temporal-order thresholds than control subjects. The detection of an association between temporal processing and speech processing, however, depended on the stimuli and the phoneme-discrimination tasks used. Our results also suggest top–down feedback on phonemic processing.